Pushing the boundaries of pnictogen-bonding organocatalysis: a clash of Sb(III) versus Bi(III) - Sharma, Jyoti; Dash, Soumya Ranjan; Vanka, Kumar (ChemPhysChem, 2025)
The sigma-hole-mediated noncovalent organocatalysis involving the pnictogen (Pn) elements has thus far been explored mostly from nitrogen to antimony, with antimony identified as the most effective catalyst. Herein, density functional theory calculations have been carried out to demonstrate that tri-aryl (Ar)-substituted bismuth(III) complexes can outperform their antimony counterparts in both anion (Cl-) binding and catalytic activity. Using a range of computational methods, a good correlation between the sigma-hole strength, chloride binding affinity, and the reaction barrier is established. Notably, the findings reveal that dispersion interactions are the dominant force in catalysts with weaker sigma-holes, while electrostatic interactions prevail in catalysts with stronger sigma-holes (for the anion abstraction step). In all cases, Bi(III) catalysts emerge as the winner over the Sb(III) analogues. Additionally, beyond the primary Pn. . .Cl interactions, several secondary interactions such as Cl. . .H/F-C(Ar) and Cl-. . . H-C(Si-TBS) also play a significant role in stabilizing the transition states.
Keywords: Antimony; Bismuth; organocatalysis; pnictogen; sigma (sigma) holes

Understanding the structural characteristics of modified ceramic hollow fiber oxygen transport membranes through in silico tomography simulation study - Jogdand, Shunottara M.; Sharma, Jyoti; Khilari, Rushikesh S.; Mahajan, Digvijay P.; Patil, Prashant; Pol, Harshavardhan V.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2025)
Design and development of integrated membrane reactor systems are gaining attention as a sustainable solution capable of performing multiple functions in a single reactor. Membrane reactors made of mixed ionic-electronic conduction materials dosing pure O to the reactions can be exploited for various catalytic processes. In this case, micro- and macrostructures of the membrane surface play a significant role in the permeation performance of membranes, and understanding these parameters prior to scaling up to modules is imperative. Here, 3D X-ray tomography imaging, a versatile nondestructive instrumental technique, is used in understanding the structural behavior of the membrane walls at different structural alignments, leading to anticipation of fouling areas upon assembling membrane reactors. La0.6Sr0.4Co0.2Fe0.8O3-delta hollow fiber membranes are fabricated by the phase inversion method and further modified by the optimized acid etching technique. In silico simulations on different morphologies before and after surface modifications are carried out under varying flow rates at nonambient temperatures to mimic real experimental conditions. Critical parameters such as gas velocity, pressure exerted on cavity walls, and strain, dictating structural integrity of the fibers under experimental conditions, were evaluated. As a result of the assessment, the surface-modified structural morphology with finger-like cavities initiating from the inner wall of the membrane was found to be robust. Increase in the pore size, nonuniform pore size distribution, and irregular and interdigitated cavities formed in outer fingered membranes after multiple surface treatments led to an similar to 5 fold increase in the average pressure exerted at the cavity walls when compared to inner fingered membranes. Strain profile generated for inner fingered membranes shows homogeneous distribution of strain for the applied stress throughout the 3D geometry of the membrane. This detailed structural analysis of the membrane will help in building a more robust and efficient system for scale-up applications.
Keywords: 3D X-ray tomography; in silico simulation; oxygen transport membranes; perovskite; phase inversionmethod

Magnesium-ligand cooperation enables regioselective transfer hydrogenation of quinolines to 1,2-dihydroquinolines - Mahata, Biplab; Sharma, Jyoti; Vanka, Kumar; Sen, Sakya S. (Organic Letters, 2026)
We report the first magnesium-catalyzed regioselective reduction of quinolines to 1,2-dihydroquinolines, utilizing H3N & centerdot;BH3. This protocol operates under mild conditions and tolerates a broad range of functional groups. Comprehensive mechanistic investigations, including kinetic analysis, deuterium labeling, and density functional theory calculations, elucidate a concerted hydride transfer pathway. This work serves as a blueprint for employing s-block metals with high-precision reactivity, which are traditionally reserved for transition metals.